RESULTS OF BOTULINUM TOXIN A INJECTION COMBINED WITH PHYSICAL THERAPY IN REHABILITATION FOR STROKE PATIENTS WITH LOWER LIMB SPASTICITY (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the outcomes of Botulinum toxin type A injection combined with therapeutic exercise in functional rehabilitation for stroke patients with lower-limb spasticity.Subjects and methods: This prospective, uncontrolled interventional study was conducted at the Rehabilitation Center of Bach Mai Hospital over a one-year period (from October 2024 to October 2025) in 24 patients with a confirmed diagnosis of hemiplegia due to stroke and moderate to severe lower-limb spasticity. The modified Ashworth scale (MAS) was used to assess spasticity severity, the Tinetti scale was used to evaluate balance and gait, the TUGT was used to assess mobility and fall risk, and the LEFS was used to evaluate lower-limb function. Values were analyzed and compared before intervention and at 1 month and 3 months after intervention.Results: After 1 month and 3 months of treatment, LEFS scores, Tinetti, TUGT, and MAS all showed significant improvement compared with baseline (p < 0.05).Conclusion: Botulinum toxin type A injection combined with therapeutic exercise significantly improves lower-limb motor function, gait, and spasticity in patients after stroke.
Keywords: Botulinum toxin, lower-limb spasticity, stroke.